Environmental & architectural phenomenology. Vol. 21, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2010)
Vol. 21, No. 2, Spring 2010 (includes “items of interest,” “citations received,” a book review by Eva-Maria Simms, essays from Julio Bermudez & Dennis Skocz, and poems by Vicki King).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals